Balance de los cuarenta años del Departamento de Sociología de la Universidad de Antioquia (2008)
ABSTRACT: In this paper the authors describe the process experienced by Sociology while becoming a profession through an academic program at the University of Antioquia since 1968. The central thesis that we discuss is that the thought and understanding of social disciplines in Colombia has disregarded the study of the role performed by local Universities, and this has been an obstacle for a more balanced and accurate view on the evolution of the Sociological discipline in Colombia. This paper offers a panoramic view on the different stages and challenges faced by the Sociology program at the University of Antioquia, highlighting the discussions and reflections developed by faculty and students regarding the definition of academic contents, and the orientation and characteristics that the curriculum should have; particularly, we show the debate generated along these forty years between an empiric Sociology and a theoretical Sociology, and the necessity of keeping different paradigmatic approaches in the curriculum, in order to offer guidance towards an understanding of the social reality in Colombia. In general, this article remarks the importance of encouraging the investigative factor as an essential element in the sociological formation that, along with rigorous theoretical grounds, guarantees the formation of an integral sociologist committed with the country’s problems.